The Potential Impact of AEC 2015 on the Small Farmers of Myanmar - Chhani, Lalrin (Asian Business Review, 2016)
The aim of this study is to find out the potential impact of AEC by comparing the farmers’ and the government officials’ perspective, and then find a solution for the farmers’ problem by using AEC. The research was done by discussing with six farmers’ family and three government officials. The participating farmers were chosen with the help of the government officials. The participants of the government can be divided into two, the one who had direct contact with the farmers and the one who formulate agriculture plans and development of agriculture sector.The significant research findings were the following: 1) Problems and challenges of the farmers in the current situation; 2) How did the farmers perceived and understand the AEC?; 3) What were the farmers’ expectations and how did they prepare for the AEC?; 4) How did the government perceive the AEC?; 5) What will the potential impact of the AEC be for the small land farmers in Myanmar?; and 6) What should the farmers do in order to solve their problems and make wise use of the AEC?
Keywords: Small Farmers; problem solving; potential impact of AEC